EVALUASI PENGELOLAAN BUMKAM DALAM MENINGKATKAN PENDAPATAN ASLI KAMPUNG DOYO BARU KABUPATEN JAYAPURA - Marbase, Junno Roberto; Aedah, Nur; Tebay, Vince (Universitas Cenderawasih, 2024)
This research aims to evaluate the management of BUMKam (Village-Owned Enterprises) in increasing the Original Income of Doyo Baru Village in Jayapura Regency, as well as analyzing the supporting and inhibiting factors. This research is important to support the economic independence of Doyo Baru Village through effective and efficient BUMKam management. This research uses a qualitative research approach with a research location in Doyo Baru Village, Waibu District, Jayapura Regency. With data collection techniques, namely interviews, observation, and documentation. data analysis includes data reduction stages, data display, and conclusion drawing and verification. The results of this study indicate that in terms of effectiveness, success lies in fulfilling the previously planned program. Efficiency, has been maximized. Adequacy, has met the needs of the village community. Equality, the community enjoys the Village-Owned Enterprise program because its management involves the village community. Responsiveness, the community has a good response because it provides satisfaction to the target group. Accuracy, has been carried out well because the program implementation system has been implemented. Supporting factors, the community and administrators motivate each other in running the program, while inhibiting factors, not all people are involved in program management.